National Liberation Narratives - Cromer, Gerald (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2006)
Abstract An analysis of the propaganda of the Freedom Fighters for Israel, one of the three movements that took up arms against the British mandate in Palestine, provides the basis for the development of a model of national liberation narratives. It indicates that they are best understood as a morality play between the forces of good and evil in which the freedom fighters will overcome seemingly insurmountable odds and ultimately emerge victorious. This configuration is repeat ed in a series of nested narratives — contemporary, historical and metahistorical, national, and universal, individual and collective — that reinforce each other and the message they are trying to convey. At the same time, however, these stories are in dialogue with three rival ones — the foreign narrative of the occupying power, the dominant narrative of less militant nationalists, and the prior narrative of the religious authorities. To a large extent, these opposing tales provide the inferential structure for the stories of the liberation movement. In the war of words, it is not the freedom fighters but their rivals that set the contours of the conflict.